Cautionnement et assurance : caractéristiques et distinctions - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1991)
This article examines the financial operations of a surety bond company. Part One mainly deals with the technical aspects of suretyship such as its definition, goals, effects, qualification criteria and the different types of bonds. Part Two is a concise analysis of two legal books on the subject written by Me Edouard Martin and Me Louise Poudrier-Lebel.